1999
DOI: 10.1142/s0217732399001280
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Anisotropy in Black Body Radiation Viewed Through Non-Uniform Gaseous Matter

Abstract: A nonlocal gauge symmetry of a complex scalar field, which can be trivially extended to spinor fields, was demonstrated in a recent paper (Mod. Phys. Lett. A13, 1265 (1998), hep-th/9902020). The corresponding covariant Lagrangian density yielded a new, nonlocal quantum electrodynamics. In this letter we show that as a consequence of this new QED, a black body radiation viewed through gaseous matter appears to show a slight deviation from the Planck formula, and propose an experimental test to check this effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…However, if we agree to define that the atom has been excited, i.e. the matrix element has come into existence, at the time t = 0, then it is a In [2] we also discuss why the cosmic background explorer (COBE ) satellite measurements of the CMBR spectrum [4] do not show this feature. b The restriction, that the particles must be subject to electromagnetic interactions, simply reflects the present status of the theory (which is undergoing continual development), and there seems to be no reason why it should be fundamental ; work is in progress to see if it can be removed.…”
Section: Theory and Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, if we agree to define that the atom has been excited, i.e. the matrix element has come into existence, at the time t = 0, then it is a In [2] we also discuss why the cosmic background explorer (COBE ) satellite measurements of the CMBR spectrum [4] do not show this feature. b The restriction, that the particles must be subject to electromagnetic interactions, simply reflects the present status of the theory (which is undergoing continual development), and there seems to be no reason why it should be fundamental ; work is in progress to see if it can be removed.…”
Section: Theory and Resultsmentioning
confidence: 91%
“…Some time ago [1] we obtained a result that matter fields possess a non-local U(1) gauge transformation symmetry that necessitates invoking a non-local electromagnetic field, and that a non-thermodynamic arrow of time at the quantum (atomic) level is enforced upon us as a necessary condition for conservation of energy in matter-radiation interactions. Based upon this result, it was subsequently predicted [2] that the spectrum of a blackbody radiation passing through gaseous matter would show an apparent deviation from the Planck formula. A very simple experimental test for verifying this prediction has been suggested in [2], where it was also shown that the results of a balloon-borne measurement [3] of the cosmic microwave background radiation (CMBR) spectrum does seem to show such a feature a .…”
Section: Introductionmentioning
confidence: 99%
“…First, whether such a deviation from the Planck distribution as predicted by our theory does occur at all is a question that can only be settled by experiment ; one possible experimental test has been suggested in [5]. Secondly, the viability of such a correlated twophoton absorption process under conditions of Woody and Richards' balloon measurements has also been established in [5]. Therefore, subject to the condition that our prediction is experimentally verified, we can claim that the CMBR travelling through tenuous matter can satisfy the condition for second-order coherence and hence, as laid down by the nonlocal QED, is capable of giving rise to correlated two-photon absorption throughout the universe -thus offering a very simple picture of the arrow of time in the entire universe at the quantum (atomic) level as a necessary condition for energy conservation.…”
mentioning
confidence: 92%
“…signal and idler photons. Very recently we have shown [5] that a third, cosmological setting is provided by this universe through the via media of the cosmic microwave background radiation (CMBR). Indeed, we can call the CMBR the "Lowest common denominator" from the viewpoint of this paper, in the sense that it influences each particle of the universe capable of interacting with an electromagnetic field .…”
mentioning
confidence: 99%
See 1 more Smart Citation